Experimental Evidence for Universal Behavior of Ion-Induced Volume Phase Transition in Sodium Polyacrylate Gels - Mussel, Matan (J Phys Chem Lett, 2019)
Introduction of high valence counterions into polyelectrolyte gels results in a reversible volume phase transition. In the present work new experimental results are reported for the volume transition induced by calcium/sodium exchange in sodium polyacrylate gels. The effects of cross-link density, concentration of ionized groups on the network chains, composition of the equilibrium salt solution containing both mono- and divalent cations, and temperature on the swelling degree of these gels are systematically investigated. It is demonstrated that the normalized swelling data fall on a master curve, indicating that the ion-exchange-induced volume transition exhibits universal behavior in sodium polyacrylate gels. Model calculations made on the basis of the classical Flory–Rehner theory are in reasonable agreement with the measured dependencies.